2014
DOI: 10.4111/kju.2014.55.9.587
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficacy of Contrast-Enhanced Ultrasound for Small Renal Masses

Abstract: PurposeUltrasound (US) is highly sensitive in the detection of renal masses. However, it may not be able to differentiate benign and malignant lesions in smaller masses. The purpose of this study was to determine the diagnostic efficacy of contrast-enhanced ultrasound (CEUS) for small renal masses.Materials and MethodsFrom January 2011 to December 2013, a total of 85 patients underwent CEUS for evaluation of renal masses. Of these patients, CEUS findings were retrospectively analyzed for small renal cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 16 publications
0
34
1
Order By: Relevance
“…The sensitivity and specificity of CEUS were 86.8% and 63.36%, respectively. Their findings were slower than that of the present study . Wei and his colleagues also compared the diagnostic efficiency of CEUS with that of contrast‐enhanced CT in 118 patients with the small renal masses.…”
Section: Discussioncontrasting
confidence: 70%
“…The sensitivity and specificity of CEUS were 86.8% and 63.36%, respectively. Their findings were slower than that of the present study . Wei and his colleagues also compared the diagnostic efficiency of CEUS with that of contrast‐enhanced CT in 118 patients with the small renal masses.…”
Section: Discussioncontrasting
confidence: 70%
“…However, it has limited use when attempting to differentiate between RCC and AML because of its lower accuracy in the characterization of some renal masses [7]. To the extent known, hypoechoic renal masses are mostly considered to be malignant while hyperechoic and iso-echoic renal masses are often referred to as benign.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings were consistent with the results of previous studies. In a prospective study of 49 lesions (38 RCCs and 11 AMLs), Oh et al (15) reported that CEUS had a sensitivity of 86.8%, a specificity of 63.6%, an accuracy of 81.6%, a positive predictive value of 89.2% and a negative predictive value of 58.3%. In a study of 137 lesions (117 RCCs and 20 AMLs), Ignee et al (6) reported that CEUS had a sensitivity of 97%, a specificity of 45%, an accuracy of 90%, a positive predictive value of 91%, and a negative predictive value of 75%.…”
Section: Discussionmentioning
confidence: 99%